Legal and Organizational Issues of the Transformation of Public Universities into Non-Profit Organizations in Kazakhstan - ALTYNBASSOV, Bakhyt; ABDUKARIMOVA, Zaure; BAYANBAYEVA, Aigerim; MUKHAMEJANULY, Sabit (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020, 2020)
This article discusses several legal and economic problems in the process of globalization of higher education in Kazakhstan. To date, the Government of Kazakhstan has issued a resolution on the transformation of 25 national and state universities into non-profit joint-stock companies, as well as amendments to the Civil Code and other current legislation. As a result of this study, it has been found that the concept of a non-profit joint-stock company was first used in Kazakhstan and contradicted the institution of legal entities in civil law. Such changes and amendments in civil law are an unprecedented phenomenon in the legal systems of the Commonwealth of Independent States (CIS) countries. There is also a risk that the transfer of higher education institutions to non-profit joint-stock companies may become the legal basis for the illegal privatization of public universities. The authors suggest that the privatization of higher education institutions has been detrimental to the state, and that reform should be addressed based on administrative and legal considerations and through improved university governance models. The modernization of the governance model of public universities according to modern requirements is beneficial to the state and society. The study analyzes the relationship between the university and its stakeholders based on Freeman’s Stakeholder theory. It also identifies deficiencies in legislation that impede the establishment of partnerships between the university and industrial companies and suggests ways to address them.